Characterization, inclusion mode, phase-solubility and in vitro release studies of inclusion binary complexes with cyclodextrins and meglumine using sulfamerazine as model drug - Aloisio, Carolina [UNESP]; Oliveira, Anselmo Gomes de [UNESP]; Longhi, Marcela (Informa Healthcare, 2014)
In order to investigate the effect on the aqueous solubility and release rate of sulfamerazine (SMR) as model drug, inclusion complexes with beta-cyclodextrin (beta CD), methyl-beta-cyclodextrin (M beta CD) and hydroxypropyl-beta-cyclodextrin (HP beta CD) and a binary system with meglumine (MEG) were developed. The formation of 1: 1 inclusion complexes of SMR with the CDs and a SMR: MEG binary system in solution and in solid state was revealed by phase solubility studies (PSS), nuclear magnetic resonance (NMR), Fourier-transform infrared spectroscopy (FT-IR), thermal analysis and X-Ray diffractometry (XRD) studies. The CDs solubilization of SMR could be improved by ionization of the drug molecule through pH adjustments. The higher apparent stability constants of SMR:CDs complexes were obtained in pH 2.00, demonstrating that CDs present more affinity for the unionized drug. The best approach for SMR solubility enhancement results from the combination of MEG and pH adjustment, with a 34-fold increment and a S-max of 54.8 mg/ml. The permeability of the drug was reduced due to the presence of beta CD, M beta CD, HP beta CD and MEG when used as solubilizers. The study then suggests interesting applications of CD or MEG complexes for modulating the release rate of SMR through semipermeable membranes.
Keywords: Complexation; cyclodextrin; meglumine; permeability; sulfamerazine